Sosialisasi Izin PIRT Produk bagi Siswa dan Guru SMAN 2 Karang Intan: Dissemination of PIRT Product Licensing Information for Students and Teachers at SMAN 2 Karang Intan - Gusti Muhammad Raja Putra Perdana; Nurbidayah Nurbidayah; Abdurrahman Abdurrahman; Eka Rusliana (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Understanding product legality is a crucial aspect of school entrepreneurship development, yet it is often overlooked. This activity aimed to increase literacy on Home Industry Food (PIRT) licensing, particularly regarding food safety standards and product labeling procedures, among students and teachers at SMAN 2 Karang Intan. The methodology used included interactive counseling, lectures, and focus group discussions (FGDs) using visual media of product packaging samples. Activity evaluation used a one-group pre-test and post-test design to measure the increase in participant knowledge. The results show a significant increase in participants' understanding of the urgency of distribution permits and the administrative requirements for SPP-IRT submission, as well as their ability to identify food labels that meet BPOM standards. It is concluded that socialization methods accompanied by label check simulations are effective in introducing business licensing procedures in an applicable manner to the school community.